2022
DOI: 10.3390/ijerph19042219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated with Postpartum Depression during the COVID-19 Pandemic: A Literature Review and Meta-Analysis

Abstract: Background: Owing to the high prevalence and detrimental consequences, postpartum depression (PPD) has been identified as one of the severe global public health issues in the last decade. Prior research found that during disasters or events, the prevalence rates of mental disorders among postpartum women are significantly high. However, the effect of the coronavirus disease 2019 (COVID-19) pandemic on PPD and its risk factors remained unclear for postpartum women. Therefore, the present systematic review and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 40 publications
9
68
2
5
Order By: Relevance
“…The researchers also point to the need for a study on the prevalence of PPD in the middle and low-income countries. 7 According to the results of multivariate logistic regression, dissatisfaction with living conditions and cohabitation with the husband/ partner's parents was found to be a significant predictor of PPD. One possible explanation for this is the importance of cultural norms in the country.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The researchers also point to the need for a study on the prevalence of PPD in the middle and low-income countries. 7 According to the results of multivariate logistic regression, dissatisfaction with living conditions and cohabitation with the husband/ partner's parents was found to be a significant predictor of PPD. One possible explanation for this is the importance of cultural norms in the country.…”
Section: Discussionmentioning
confidence: 98%
“…6 However, more recently, the results of studies on the prevalence of PPD during the COVID-19 pandemic indicate two times (34% (95% CI: 21-46%)) higher prevalence of PPD among women than before the non-pandemic. 7 It is also worth noting that there are lack of papers to identify PPD in Central Asian countries, including Kazakhstan. 6 Kazakhstan achieved the Millennium Development Goal (MDG) 5 of reducing maternal mortality ratio and achieving universal access to reproductive health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of the child was considered a confounder and was adjusted for in our model. (26,28,(37)(38)(39)(40)(41)(42)(43). The studies that found higher stress levels were carried out at the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…While this is an astonishing trend, pregnant individuals were even more severely impacted. Prior to the global COVID-19 pandemic, the pooled prevalence of perinatal depression was found to be 11.9%, and postpartum depression was identified among approximately 10-15% of mothers in developed countries [9][10]. As of 2022, the pooled prevalence of depression was subsequently found to be 34% in postpartum individuals, an almost 10% difference from the general population and as high as a 24% increase from the postpartum depression prevalence pre-pandemic [9].…”
Section: Editorialmentioning
confidence: 99%